Musculoskeletal System of Huge Tarsometatarsal Region in the Dong Tao Fowls from North Vietnam - Hideki Endo; Naoki Tsunekawa; Kohei Kudo; Yoshihiro Hayashi; Kazunobu Ikeya; Nguyen Truong Son; Fumihito Akishinonomiya (The Journal of Poultry Science, 2017)
A macroscopic examination of the huge leg of the Dong Tao breed from North Vietnam was conducted. Bone and muscular tendon morphometric data demonstrated that the Dong Tao breed was equipped with the extraordinarily thick and large tarsometatarsal bone and distal parts of the related tibiotarsus regions. Morphological differences between dorsal and plantar sides were clearly observed. First, on the dorsal side, fleshy bundles were extended effectively using the enlarged dorsal surface of tarsometatarsal bone shown as Musuculus extensor digitorum brevis, M. extensor digiti I brevis and M. adductor digiti IV. The strong and fleshy extensor bellies of M. tibialis cranialis and M. extensor digitorum longus were enlarged in the crural region, functioning to dorsally pull the heavy tarsometatarsal region through the ankle joint. Second, on the plantar side, the flexor tendon groups around the ankle joint were wider and thicker than those of other ordinary breeds, possibly to stabilize the tarsometatarsal bone and to flex the phalange as observed in M. flexor perforatus digiti II, M. flexor perforans et perforatus digiti II, M. flexor perforatus digiti III, M. flexor perforans et perforatus digiti III, M. flexor perforatus digiti IV, and M. flexor perforans digitorum profundus. The mass of the huge tarsometatarsal region does not contribute to effective locomotion in the Dong Tao fowl in comparison with that associated with normal breeds. However, we suggest that these morphological changes in the musculoskeletal system may functionally compensate for the physical disadvantages of the large weight of the distal part of the hindlimb in the Dong Tao fowl.